Return to "0": A Lacanian Reading of Ingeborg Bachmann's "Undine Goes" - Veronica P. Scrol (Studies in 20th & 21st Century Literature, 1994)
This essay approaches Ingeborg Bachmann's "Undine Goes" from a Lacanian perspective. The object of the study is three-fold: first, to demonstrate Bachmann's deconstruction of the ideal ego through the water-sprite Undine's criticism of the human Hans. Second, to transcend the limitations of dualistic interpretations (as noted by some feminist critics), by introducing the triple Lacanian registers—the imaginary, the symbolic, and the real—into this particular reading. Finally, to establish Bachmann's monologic text as a discourse of the real and Undine as the voice of the death instinct.
Keywords: Ingeborg Bachmann; Undine Goes; Lacanian perspective; Lacanian reading; deconstruction; ideal ego; water-sprite; criticism; human; Hans; limitations of dualistic interpretations; dualistic interpretations; feminist critics; triple Lacanian registers; imaginary; symbolic; real; monologic text; discourse; death instinct; voice